2018
DOI: 10.20944/preprints201801.0037.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biological Effects of Amelogenin Exon 5 Encoded Peptide from Enamel Matrix Derivative in Human Dental Pulp Cells

Abstract: Enamel matrix derivative (EMD) is used for periodontal tissue regeneration therapy, and 17can induce mineralization in dental pulp cells (DPCs). We designed a synthetic peptide (SP) derived

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…In line with this data, with the use of Multiplex ELISA (using commercially-customized U-PLEX human biomarkers) in our study, we showed that UV-C-killed bacteria significantly induced pro-inflammatory cytokines secretion-IL-6, IL-8, IL-1b and granulocyte macrophage colony-stimulating factor (GM-CSF)-especially by gram-negative F. nucleatum and grampositive P. yurii. Consistent with our results, several studies showed that LPS of periodontal pathogen P. gingivalis and LPS from E. coli can stimulate the secretion of the same pro-inflammatory cytokines IL-6 and IL-8 in periodontal-ligament-derived, gingiva-derived MSCs and SCAP (Wang and Ohura, 2002;Jönsson et al, 2008;Trubiani et al, 2012;Herath et al, 2013;Wang et al, 2013;Kato et al, 2014;Andrukhov et al, 2016;Diomede et al, 2017). This proinflammatory cytokines secretion was also observed for grampositive P. yurii, which exerts the LTA ligand for TLR2, and it was shown by several studies that induction of TLR2 in human periodontal-ligament-derived stem cells also resulted in the upregulation of IL-8, IL-6, and MCP-1 (in our study we did not observe the statistically significant increase of the MCP-1, except the trend towards it) (Blufstein et al, 2018;Behm et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with this data, with the use of Multiplex ELISA (using commercially-customized U-PLEX human biomarkers) in our study, we showed that UV-C-killed bacteria significantly induced pro-inflammatory cytokines secretion-IL-6, IL-8, IL-1b and granulocyte macrophage colony-stimulating factor (GM-CSF)-especially by gram-negative F. nucleatum and grampositive P. yurii. Consistent with our results, several studies showed that LPS of periodontal pathogen P. gingivalis and LPS from E. coli can stimulate the secretion of the same pro-inflammatory cytokines IL-6 and IL-8 in periodontal-ligament-derived, gingiva-derived MSCs and SCAP (Wang and Ohura, 2002;Jönsson et al, 2008;Trubiani et al, 2012;Herath et al, 2013;Wang et al, 2013;Kato et al, 2014;Andrukhov et al, 2016;Diomede et al, 2017). This proinflammatory cytokines secretion was also observed for grampositive P. yurii, which exerts the LTA ligand for TLR2, and it was shown by several studies that induction of TLR2 in human periodontal-ligament-derived stem cells also resulted in the upregulation of IL-8, IL-6, and MCP-1 (in our study we did not observe the statistically significant increase of the MCP-1, except the trend towards it) (Blufstein et al, 2018;Behm et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Siqueira, 2019). It was shown that LPS of gram-negative bacteria, LTA of gram-positive, and bacterial lipoproteins can stimulate mesenchymal stem cells inflammatory response, and reduce their osteogenic potential (Tom-Kun Yamagishi et al, 2011;Morsczeck et al, 2012;Kato et al, 2014;Nguyen and Götz, 2016;Yu et al, 2019;Lei et al, 2020;Yin et al, 2020;Casey et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, remaining pathogens alter the induced release of TGF-β1 from dentin (Cameron et al, 2019). Bacterial lipopolysaccharides could also remain after root canal disinfection and promote pro-inflammatory cytokines production (Kato et al, 2014). Additionally, induction of an inflammatory periapical plug was demonstrated to hinder cell migration into the root canal and subsequently prevent tissue regeneration (Zaky et al, 2020).…”
Section: Disinfection and Regeneration; A Cause-and-effect Relationsh...mentioning
confidence: 99%
“…Many studies have established the immunobiological importance of the lipopolysaccharide of Gram negative cell wall envelope (127,128). It has the ability to activate the host inflammatory responses and disrupt bone remodeling process (129,130). P. gingivalis LPS binds to the CD14 and TLR-4, activating macrophages, epithelial cells respectively, leading to secretion of pro-infammatory cytokines (131,132).…”
Section: Lipopolysaccharides (Lps)mentioning
confidence: 99%